Congenital Ocular Neuromyotonia with Partial Third Nerve Palsy. Issue 1 (2nd January 2019) - Thompson, Barrett; Kerr, Natalie; Bell, Austin; Graves, Emily; McGregor, Amy
ABSTRACT: Purpose: We report the first case of congenital ocular neuromyotonia (ONM) and the results of strabismus surgery for this patient's co-existing cranial nerve (CN) III palsy. Patients and method: The patient presented at 18 months with strabismus that had reportedly been present since the time of birth. On exam, she had persistent exotropia (RXT) and hypertropia (RHT) with episodes of esotropia in the right eye that could be evoked by sustained left gaze. A diagnosis of ONM with partial CN III palsy was made. T1-weighted, T2-weighted, and fluid-attenuated inversion recovery magnetic resonance imaging failed to reveal intracranial pathology. Results: Gaze induced intermittent esotropia resolved with carbamazepine. Surgery was performed to improve the patient's RXT and RHT. Post-operatively, the patient's RXT had improved from 12 to 15 prism diopters (∆) at near and 20∆ at a distance to 10∆ RXT at near with no horizontal deviation at distance. Her deviation has remained stable for 13 years, as has her neurological exam and good state of health. Conclusion: This case demonstrates that ONM may present congenitally and adds to the body of knowledge regarding surgical outcomes on concurrent CN palsies in these patients.